1953
DOI: 10.33915/agnic.361t
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative nutritional status studies in the Northeast Region.

Abstract: CONTENTSPace IO © r-l r-l CO rl CO tH CO * t-CO © © N r(r( N rH rH H IN © IN u

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1955
1955
1969
1969

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 3 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Babcock et al (4) reported that only 3 per cent of the children under 13 years of age studied in New York state showed signs of cheilosis, and less than 1 per cent of the children in this age group had mild cases of gingivitis. Less than 5 per cent of the 13to 15-year-old subjects showed signs of cheilosis, and less than 1 per cent showed signs of gingivitis.…”
Section: General Discussion Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Babcock et al (4) reported that only 3 per cent of the children under 13 years of age studied in New York state showed signs of cheilosis, and less than 1 per cent of the children in this age group had mild cases of gingivitis. Less than 5 per cent of the 13to 15-year-old subjects showed signs of cheilosis, and less than 1 per cent showed signs of gingivitis.…”
Section: General Discussion Of Resultsmentioning
confidence: 99%
“…Mild to moderate cases of gingivitis were noted for all age groups and might have been caused by a deficiency of ascorbic acid (18,19,20). About 30 per cent of the 7to 9-year-old children and 35 per cent of the 10to 12-year-old children showed gingivitis.…”
Section: Medical Inspectionsmentioning
confidence: 95%
See 3 more Smart Citations